PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT ISLAM (RSI) SITI RAHMAH - M.Pd, Tri Irfa Indrayani (MENARA EKONOMI, 2018)
The purpose of this study (1) To determine the effect of service quality on patient satisfaction in RSI Siti Rahmah, (2) To determine the effect of facilities on patient satisfaction in RSI Siti Rahmah,(3) To know the Influence of Service Quality and Facilities to Patient Satisfaction at RSI Siti Rahmah. The method used in this research is Quantitative Method with Multiple Linear Regression analysis using Label Scale. The population of this study were 100 inpatients in RSI Siti Rahmah in Room, Maternity Room (KB) and the number of samples in this study were 50 patients with random sampling method, using Slovin formula. Methods of data collection by distributing questionnaires. The results showed that service quality significantly influence patient satisfaction. thitung> ttable that is tcount 2.85 > t table 2.12. Significant level of 0.007 <0.05. The first hypothesis (H1) is accepted. Facilities have a significant effect on patient satisfaction. T hitung 2.91 > t table 2.12. Significant value 0.006 <0.05. The second hypothesis (H2) is accepted. Quality of service and facilities on patient satisfaction Fcount 1.834> Ftabel 0.012. With a significant level of 0.171> 0.05. This shows that there is no significant influence. The third hypothesis in this study (H3) was rejected.Keywords: Service Quality, Facilities, Patient Satisfaction